A plea for descriptive social ontology - Koslicki, Kathrin; Massin, Olivier (My University, 2023)
Abstract Social phenomena—quite like mental states in the philosophy of mind—are often regarded as potential troublemakers from the start, particularly if they are approached with certain explanatory commitments, such as naturalism or social individualism, already in place. In this paper, we argue that such explanatory constraints should be at least initially bracketed if we are to arrive at an adequate non-biased description of social phenomena. Legitimate explanatory projects, or so we maintain, such as those of making the social world fit within the natural world with the help of, e.g., collective intentionality, social individualism, and the like, should neither exclude nor influence the prior description of social phenomena. Just as we need a description of the mental that is not biased, for example, by (anti)physicalist constraints, we need a description of the social that is not biased, for example, by (anti)individualist or (anti)naturalist commitments. Descriptive social ontology, as we shall conceive of it, is not incompatible with the adoption of explanatory frameworks in social ontology; rather, the descriptive task, according to our conception, ought to be recognized as prior to the explanatory project in the order of inquiry. If social phenomena are, for example, to be reduced to nonsocial (e.g., psychological or physical) phenomena, we need first to understand clearly what the social candidates for the reduction in question are. While such descriptive or naïve approaches have been influential in general metaphysics (see Fine 2017), they have so far not been prominent in analytic social ontology (though things are different outside of analytic philosophy, see esp. Reinach (1913). In what follows, we shall outline the contours of a descriptive approach by arguing, first, that description and explanation need to be distinguished as two distinct ways of engaging with social phenomena. Secondly, we defend the claim that the descriptive project ought to be regarded as prior to the explanatory project in the order of inquiry. We begin, in Section 2, by considering two different ways of engaging with mental phenomena: a descriptive approach taken by descriptive psychology and an explanatory approach utilized in analytic philosophy of mind. We take these two ways of approaching the study of the mind to be analogous to the distinction we want to draw in social ontology between a descriptive and an explanatory approach to the study of social phenomena. We consider next, in Section 3, how our approach compares to neighboring perspectives that are familiar to us from general metaphysics and philosophy more broadly, such as Aristotle’s emphasis on “saving the appearances”, Strawson’s distinction between descriptive and revisionary metaphysics, as well as Fine’s contrast between naïve and foundational metaphysics. In Section 4, we apply the proposed descriptive/explanatory distinction to the domain of social ontology and argue that descriptive social ontology ought to take precedence in the order of inquiry over explanatory social ontology. Finally, in Section 5, we consider and respond to several objections to which our account might seem to be susceptible.
Keywords: Descriptive metaphysics · Social ontology · Explanation · Description · Phenomenology · Revisionary metaphysics · Appearances · Metametaphysics